New Records of two Impatiens species (Balsaminaceae) and updated distribution notes on Impatiens falcifera in Bhutan - Gyeltshen , P.; Tobgay , P.; Tobgay, K.; Phuentsho, P. (Rheedea, 2025)
Two species of Impatiens, viz., I. gamblei Hook.f. and I. laevigata Wall. ex Hook.f. & Thomson, are reported here as new additions to the flora of Bhutan. Additionally, the distribution of I. falcifera Hook.f. in Bhutan is discussed. Impatiens falcifera and I. gamblei belong to sect. Racemosae, while I. laevigata is classified in sect. Semeiocardium based on four-carpellate ovary.